Z–Source Multilevel Inverter Based on Embedded Controller - K. Vijayalakshmi; Chinnapettai Ramalingam Balamurugan (Institute of Advanced Engineering and Science, 2017)
In this paper Embedded based Z-source multilevel inverter (ZSMLI) is proposed. This work implements a five level cascaded H-bridge Z-source inverter by using embedded control. Switching devices are triggered using embedded controller. In this controller coding is described by using switching table. The presence of Z-source network couples inverter main circuit to the power source that providing special features that can overcome the limitations of VSI (voltage source inverter) and CSI (current source inverter). The Z-source concept can applicable in all dc-ac, dc-dc, ac-dc and ac-ac power conversions. Simulation model of Z-source multilevel inverter based on embedded controller has been built in MATLAB/SIMULINK. The Performance parameters of Z-source MLI such as RMS (root mean square) output voltage, THD (total harmonic distortion) and DC component have been analysed for various inductance (L) and capacitance (C) value.